115 Multi-Disciplinary Simulation Training on Delirium. (16th March 2021) - Varma, S; Alston, D; Shah, B; Long, S
Abstract: Introduction: Delirium is still perceived as a "geriatric medicine competency", despite its high prevalence across most specialties. Collective multi-disciplinary team performance in implementation of multi-component interventions is key. Simulation training incorporates the complex interplay of non-technical factors, specifically, role recognition and empowerment, inter-personal skills and teamwork that are pivotal in delivering effective delirium care. Methods: Funding was approved by Health Education England. 2 pilot teaching sessions were arranged in the simulation ward. 3 scenarios were developed, each requiring a facilitator, an actor and three participants- a foundation-year doctor, a nurse/healthcare assistant and a therapist. Scenario 1 dealt with a patient with hypoactive delirium with focus on identification and multidisciplinary optimisation. Scenario 2 challenged participants with management of an agitated patient. Scenario 3 involved discharging a patient with resolving delirium and a reluctant relative, with emphasis on mental capacity assessment. Communication, patient risk assessment and challenging perceived role barriers were global themes. Participant feedback was captured using unstructured interviews and pre- and post-session 5-point Likert confidence scale in various learning outcomes. Results: 16 participants were included- 4 foundation year doctors, 3 therapists, 2 healthcare assistants and 7 nurses. There was an average improvement in Likert confidence scales in all measured learning outcomes. All participants would recommend the course to their colleagues (average Likert scale 4.9). Qualitative feedback appraised the course for demonstration of de-escalation communication strategies, the application of mental capacity and recognition of early discharge planning. Conclusion: Simulation training targeted at multi-disciplinary groups is an effective way to deliver teaching on delirium. It contextualises synergistic operation of different skills and personal accountability in influencing patient management. The challenge to its potential remains its adoption as mandatory training for various disciplines involved in care of older adults and its implementation at a wider-scale, to assure cost effectiveness.